Whistleblowing, Relativism, and Professionalism Mediated By Ethical Sensitivity among Government Auditors - Meliana, Meliana; Fala, Dwi Yana Amalia Sari (International Journal of Economics Development Research (IJEDR), 2024)
The revelation of several cases of violations, such as corruption, is inseparable from the role of whistleblowers. Whistleblowers as people who know for sure that there is a violation, such as auditors, are one of the keys in preventing actions that violate the provisions in the preparation of financial statements. Thus, it is very important to know the factors that influence the auditor's intention to do whistleblowing. This study aims to examine the effect of relativism ethical orientation and auditor's professionalism to whistleblowing with ethical sensitivity as a mediator. The novelty of this research is the use of ethical sensitivity as a mediator. The data collection technique in research is a survey method using a questionnaire. The sampling technique uses the census technique (saturated sample). The research sample was all auditors who worked at the North Maluku Province Inspectorate, totaling 40 respondents. The analytical method used in this research is Partial Least Squares (PLS) with a Structural Equation Modeling (SEM) equation model using SmartPLS software. The results of this research found that the relativism ethical orientation and auditor's professional have a positive effect to whistleblowing. Meanwhile, Ethical Sensitivity is a mediator in the influence between relativism ethical orientation and auditor professionalism attitudes on auditor intention to whistleblowing.